Efektifitas Gaya Kepemimpinan Dan Iklim Komunikasi Kepegawaian Terhadap Motivasi Kerja Pegawai Kepolisian Bidhumas Polda Jawa Tengah - Roseana, Brilianti; Noor Rakhmad, Wiwid (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2018)
This research was conducted to know the effectiveness of leadership style and climate of employee communication to work motivation of police officer of bidhumas of Central Java Police. Definition of theory of X-efficiency by Leibenstein a good leadership style is a leadership style that can control their subordinates by adjusting to the situation. The purpose of this study is to provide an overview to the agency and become input for Bidhumas Polda Central Java, to keep motivating its members in carrying out the tasks in order to achieve maximum results. Sampling in this research is total sampling. The population in the study were all employees of BidHumas Polda Central Java. The number of samples studied were 34 respondents.Based on the hypothesis test conducted using multiple linear regression analysis. There is influence of leadership style and climate of employee communication to work motivation of BidHumas Polda Jateng staff. This is indicated by multiple linear regression test conducted on leadership style (X1) variable, and employee communication climate (X2) on employee work motivation (Y) got significance value 0,000 (<0,05) variable Y. In the hypothesis test obtained coefficient value direction regression leadership style of 0.368, communications climate of 0.207. Suggestion given that is expected able to give description to institution and become input for Bidhumas Polda Central Java, to keep motivating its member in carrying out duty in order to achieve maximum work result.This research was conducted to know the effectiveness of leadership style and climate of employee communication to work motivation of police officer of bidhumas of Central Java Police. Definition of theory of X-efficiency by Leibenstein a good leadership style is a leadership style that can control their subordinates by adjusting to the situation. The purpose of this study is to provide an overview to the agency and become input for Bidhumas Polda Central Java, to keep motivating its members in carrying out the tasks in order to achieve maximum results. Sampling in this research is total sampling. The population in the study were all employees of BidHumas Polda Central Java. The number of samples studied were 34 respondents.Based on the hypothesis test conducted using multiple linear regression analysis. There is influence of leadership style and climate of employee communication to work motivation of BidHumas Polda Jateng staff. This is indicated by multiple linear regression test conducted on leadership style (X1) variable, and employee communication climate (X2) on employee work motivation (Y) got significance value 0,000 (<0,05) variable Y. In the hypothesis test obtained coefficient value direction regression leadership style of 0.368, communications climate of 0.207. Suggestion given that is expected able to give description to institution and become input for Bidhumas Polda Central Java, to keep motivating its member in carrying out duty in order to achieve maximum work result.